2015
DOI: 10.21608/ejrci.2015.9315
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolactin in Patients with Rheumatoid Arthritis and its Association with Disease Activity

Abstract: Background: Rheumatoid arthritis is a systemic autoimmune disease characterized by inflammatory polyarthritis. Prolactin acts as a potent immunomodulator and may play a role in disease severity and the process of joint damage in Rheumatoid arthritis. Aim of Study:The aim of this study was to evaluate the level of serum prolactin in patients with Rheumatoid arthritis and determine its association with disease activity and structural damage. Patients and Methods: The study included 40 patients with Rheumatoid ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Meanwhile, there was a non-significant difference in the DAS28 score on comparing lactating women using OCs with those non- lactating. Our results agree with Fayez et al who reported that increased level of serum prolactin was found in patients with high disease activity when compared to moderate and low disease activity and serum prolactin level was significantly correlated with DAS28 and ESR [20], also, Fojtíková et al reported that RA patients with active disease had high serum prolactin level which correlated significantly with disease activity and Larsen score [35]. Many previous studies have explored the effect of breastfeeding on disease activity during the postpartum period which is challenging for women suffering from rheumatologic diseases due to the increased risk of disease flare and limitations in the use of medications during breastfeeding [36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, there was a non-significant difference in the DAS28 score on comparing lactating women using OCs with those non- lactating. Our results agree with Fayez et al who reported that increased level of serum prolactin was found in patients with high disease activity when compared to moderate and low disease activity and serum prolactin level was significantly correlated with DAS28 and ESR [20], also, Fojtíková et al reported that RA patients with active disease had high serum prolactin level which correlated significantly with disease activity and Larsen score [35]. Many previous studies have explored the effect of breastfeeding on disease activity during the postpartum period which is challenging for women suffering from rheumatologic diseases due to the increased risk of disease flare and limitations in the use of medications during breastfeeding [36].…”
Section: Discussionsupporting
confidence: 93%
“…Prolactin is a hormone which has a cytokine-like action and is considered as an immune-stimulatory agent that is involved in synovial hyperplasia and inflammation [17,18], it is secreted by the pituitary gland in addition to macrophages and lymphocytes located in the synovial tissue of inflammatory arthritis patients [19]. Prolactin has a role in the severity of the disease and enhances RA joint damage [20]. Clinical trials revealed significantly high serum prolactin in RA patients suggesting that prolactin may have a significant role in disease activity and also in the disease development process [21].…”
Section: Introductionmentioning
confidence: 99%
“…Vasoinhibin shows positive high significant correlation between vasoinhibin and both DAS28, CDAI (p<0.001). According to Fayez et al, [29]. study on 40 RA patients Serum prolactin concentrations in patients were significantly higher.…”
Section: Resultsmentioning
confidence: 94%